The Influence of Praetorian Actions on Roman Tort Law - Bartkus, Jurgis (Teisė, 2025)
The article examines the influence of two actions created by Roman praetors, namely actio utilis and actio in factum, on the development of the main source of tort law in Rome – the Lex Aquilia. The text of the Lex Aquilia established important concepts of tort law, i.e., illegality, the principle of compensation for damage, causation, but the success of the Lex Aquilia cannot be attributed solely to the text itself. The beauty of Roman law lies in the fact that, by separating the functions of the praetor and the judge (iudex), the Romans allowed the praetors to create various actions which contributed to the interpretation of the Lex Aquilia and the formation of Roman tort law.